Causas de decomiso en la inspección sanitaria de bovinos, faenados en el Camal de la empresa pública metropolitana de rastro Quito - Tobar Montesdeoca, Matthew Daniel (2021)
The causes of confiscation in the sanitary inspection of cattle, slaughtered are the main reason for economic losses and the spread of diseases, which represent a risk to human health, animal health, the environment, wildlife, domestic animals, and the development of possible epizootics. This research is a descriptive study, a recording technique was used in which it consists, origin, pathology, sex that will determine the most frequent diseases and establish their prevalence in cattle slaughtered in the metropolitan public company of the Quito slaughterhouse, 5723 cattle were evaluated, 560 different pathologies. The city where most dystomatosis decomposes was Cotopaxi, Santo Domingo liver abscesses, Pichincha liver cirrhosis, Orellana telangiectasia, Imbabura pneumonia, Sucumbíos Hepatic steatosis, Carchi trauma. Parasitic diseases that present risk to public health have been detected in the sanitary inspection and are of zoonotic origin, distomatosis, and hydatidosis, in conclusion, a group of 7 diseases was identified with prevalence that stand out from the total of 17 pathologies analyzed, among these are distinguishes dystomatosis, liver abscesses, liver cirrhosis, telangiectasia, pneumonia, hepatic steatosis, and trauma.